The transformative influence of social media: an exploratory case study of empowerment in repressive society. (2nd August 2019) - Gadgil, Guruprasad; Prybutok, Gayle; Prybutok, Victor
The literature and the theoretical foundation in this discipline shows that little research has explored the complex decisions faced by transgender entrepreneurs in India. Our work describes a case study that serves as a first step in addressing this research gap and investigates the factors that influence entrepreneurism among transgender individuals in this restrictive culture. This qualitative research constructs a model to explain the relationships between factors that affect entrepreneurial behaviour among transgender, and then modify the model based on interview data collected from our key informant. A key finding points out the important role that social networking plays in entrepreneurial success when the transgender entrepreneur's skill set is an integral part of a small scale or family business endeavour. This study suggests future research directed at understanding the unique aspects of transgender entrepreneurism in India and informs on entrepreneurism and public policy in India about this population of entrepreneurs.